Emerging Therapeutic Targets Against Toxoplasma gondii: Update on DNA Repair Response Inhibitors and Genotoxic Drugs - Ángel, Sergio Oscar (2020)
Toxoplasma gondii is the causative agent of toxoplasmosis in animals and humans. This infection is transmitted to humans through oocysts released in the feces of the felines into the environment or by ingestion of undercooked meat. This implies that toxoplasmosis is a zoonotic disease and T. gondii is a foodborne pathogen. In addition, chronic toxoplasmosis in goats and sheep is the cause of recurrent abortions with economic losses in the sector. It is also a health problem in pets such as cats and dogs. Although there are therapies against this infection in its acute stage, they are not able to permanently eliminate the parasite and sometimes they are not well tolerated. To develop better, safer drugs, we need to elucidate key aspects of the biology of T. gondii. In this review, we will discuss the importance of the homologous recombination repair (HRR) pathway in the parasite's lytic cycle and how components of these processes can be potential molecular targets for new drug development programs. In that sense, the effect of different DNA damage agents or HHR inhibitors on the growth and replication of T. gondii will be described. Multitarget drugs that were either associated with other targets or were part of general screenings are included in the list, providing a thorough revision of the drugs that can be tested in other scenarios.